Observations of NIR polarized light from Sagittarius A*. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Shahzamanian, B.; Eckart, A.; Zamaninasab, M.; Witzel, G.; Sabha, N.
Abstract: We present a brief overview of results obtained from near-infrared polarized observations of Sgr A*, which is associated with the supermassive black hole at the center of the Milky Way. The observations have been carried out using the NACO adaptive optics instrument at the VLT UT4 in the infrared K s -band from 2004 to 2012. Several polarized flares have been observed in this time interval which allow us to determine the statistical properties of NIR linearly polarized light from Sgr A*. Linear polarization at 2.2 μm and its variations can help us to constrain the physical conditions of the accretion process around this supermassive black hole.